Synthesis of Nuevamine Aza-Analogues by a Sequence: I-MCR–Aza-Diels–Alder–Pictet–Spengler - Islas-Jácome, Alejandro; Cárdenas-Galindo, Luis E.; Jerezano, Alberto V.; Tamariz, Joaquín; González-Zamora, Eduardo; Gámez-Montaño, Rocío (Synlett, 2012)
A series of nuevamine aza-analogues were prepared in moderate to good yields in two reaction steps. The synthetic strategy involves an isonitrile-based multicomponent reaction, including an aza-Diels–Alder cycloaddition and Pictet–Spengler reaction as postcondensation.
Keywords: nuevamine aza-analogue; I-MCR; aza-Diels–Alder; S-oxidation; Pictet–Spengler cyclization